Kapabilitas Adopsi FinTech dan Kinerja Inovasi UMKM di Kota Medan: Peran Kompetensi Digital, Kepercayaan Platform, dan Efisiensi Transaksi - Anggi Pratiwi Sitorus; Salman Munthe; Muammar Rinaldi; Rossy Pratiwy Sihombing; Rusiadi Rusiadi (Jurnal EMT KITA, 2026)
This study examines how digital competence, platform trust, and transaction efficiency influence FinTech adoption capability and MSME innovation performance in Medan. Using a quantitative survey design, this study focuses on MSME owners and managers who use or have access to digital financial services. Digital competence reflects the ability to operate and integrate financial technology into business activities, while platform trust refers to confidence in the security, reliability, and credibility of FinTech services. Transaction efficiency captures perceived speed, convenience, and cost reduction in digital financial transactions. Data are analyzed using Structural Equation Modeling to test the direct effects of these factors on FinTech adoption capability and its subsequent effect on innovation performance. The expected findings indicate that MSMEs with stronger digital competence, higher platform trust, and greater transaction efficiency are more capable of adopting FinTech and improving innovation performance. This study contributes by positioning FinTech adoption capability as a strategic mechanism for strengthening MSME digital business innovation.